Stress Hormones Receptors in the Amygdala Mediate the Effects of Stress on the Consolidation, but Not the Retrieval, of a Non Aversive Spatial Task - Segev, Amir; Ramot, Assaf; Akirav, Irit (PLOS ONE, 2012)
This study examined the effects of the arousal level of the rat and exposure to a behavioral stressor on acquisition, consolidation and retrieval of a non-aversive hippocampal-dependent learning paradigm, the object location task. Learning was tested under two arousal conditions: no previous habituation to the experimental context (high novelty stress/arousal level) or extensive prior habituation (reduced novelty stress/arousal level). Results indicated that in the habituated rats, exposure to an out-of-context stressor (i.e, elevated platform stress) impaired consolidation and retrieval, but not acquisition, of the task. Non-habituated animals under both stressed and control conditions did not show retention of the task. In habituated rats, RU-486 (10 ng/side), a glucocorticoid receptor (GR) antagonist, or propranolol (0.75 µg/side), a beta-adrenergic antagonist, injected into the basolateral amygdala (BLA), prevented the impairing effects of the stressor on consolidation, but not on retrieval. The CB1/CB2 receptor agonist WIN55,212-2 (WIN, 5 µg/side) microinjected into the BLA did not prevent the effects of stress on either consolidation or retrieval. Taken together the results suggest that: (i) GR and β-adrenergic receptors in the BLA mediate the impairing effects of stress on the consolidation, but not the retrieval, of a neutral, non-aversive hippocampal-dependent task, (ii) the impairing effects of stress on hippocampal consolidation and retrieval are mediated by different neural mechanisms (i.e., different neurotransmitters or different brain areas), and (iii) the effects of stress on memory depend on the interaction between several main factors such as the stage of memory processing under investigation, the animal's level of arousal and the nature of the task (neutral or aversive).